Social Inequality in the Movie Fantastic Mr. Fox - Avatara, Bintang; Karima, Festi Himatu; Kustantinah, Indri; Vatsiniaina, Andriamihaja Henintsoa (Universitas PGRI Semarang, 2024)
This research examined social inequality and the resulting conflicts in the movie